Indol Acetic Acid Production of Indigenous Plant Growth Promotion Rhizobacteria from Paddy Soil - Purwanto, Purwanto; Agustono, Tridjoko; Widjonarko, Bambang Rudianto; Widiatmoko, Teguh (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2019)
The aim of this research was to examine the diversity of indigenous plant growth promoting rhizobacteria from paddy soil and to obtain a superior isolate that can support the growth and vigor of rice plants. This research was conducted in the Laboratory of Agronomy and Horticulture, Faculty of Agriculture, Jenderal Soedirman University from July to September 2017. The bacteria were isolated from paddy soil rhizosphere originated from rice production centers of Banyumas Regency i.e. Kebasen, Rawalo, Patikraja, Jatilawang, and Karangwangkal. Results showed that indigenous PGPR from paddy soil were able to produce Indol Acetic Acid (IAA) in the range 0.05-5.40 ppm, but did not have the ability to solubilize phosphate. Plant Growth Promoting Rhizobacteria (PGPR) inoculation in rice seedlings was able to increase seed vigor, plant height, root length, and seed germination. Based on morphological and biochemical characters, PGPR isolates were identified as Bacillus sp., Pseudomonas sp., Streptococcus sp., and Staphylococcus sp.